The last days of american crime ebook - Remender, Rick (The Last Days of American Crime (2009)., 2015)
The critically acclaimed, smutty, sci-fi, and noir first collaboration between RICK REMENDER (LOW, DEADLY CLASS) and GREG TOCCHINI (LOW, Uncanny X-Force) is finally back in print, remastered, and delivered in a glorious hardcover format. Collects LAST DAYS OF AMERICAN CRIME #1-3. Select praise for THE LAST DAYS OF AMERICAN CRIME: Last Days hits reader with an unflinching dose of pulp noir seediness and doesnÍt let up.î .USA Today Writer Remender layers plenty of sex and violence on top of a zinger of a story. TocchiniÍs artwork is superb. Last Days is the perfect blend of art, dialogue and gritty feel.î .WIRED Although Remender has crafted a fine crime noir, it's the socio-political aspect that won me over.î .IGN If you enjoy Criminal and other crimes books, you'll probably get a kick out of this.î .Comic Book Resources. Author: Rick Remender. Illustrator: Greg Tocchini . 2015 Rick Remender and Radical Publishing, Inc..